A chronic hypoxic response in photoreceptors alters the vitreous proteome in mice. (August 2019) - Schori, Christian; Trachsel, Christian; Grossmann, Jonas; Barben, Maya; Klee, Katrin; Storti, Federica; Samardzija, Marijana; Grimm, Christian
Abstract: Reduced oxygenation of the outer retina in the aging eye may activate a chronic hypoxic response in RPE and photoreceptor cells and is considered as a risk factor for the development of age-related macular degeneration (AMD). In mice, a chronically active hypoxic response in the retinal pigment epithelium (RPE) or photoreceptors leads to age-dependent retinal degeneration. To identify proteins that may serve as accessible markers for a chronic hypoxic insult to photoreceptors, we used proteomics to determine the protein composition of the vitreous humor in genetically engineered mice that lack the von Hippel-Lindau tumor suppressor ( Vhl ) specifically in rods (rod ΔVhl ) or cones (all-cone ΔVhl ). Absence of VHL leads to constitutively active hypoxia-inducible transcription factors (HIFs) and thus to a molecular response to hypoxia even in normal room air. To discriminate between the consequences of a local response in photoreceptors and systemic hypoxic effects, we also evaluated the vitreous proteome of wild type mice after exposure to acute hypoxia. 1′043 of the identified proteins were common to all three hypoxia models. 257, 258 and 356 proteins were significantly regulated after systemic hypoxia, in rod ΔVhl and in all-cone ΔVhl mice, respectively, at least at one of the analyzed time points. Only few of the regulated proteins were shared by the models indicating that the vitreous proteome is differentially affected by systemic hypoxia and the rod or cone-specific hypoxic response. Similarly, the distinct protein compositions in the individual genetic models at early and late time points suggest regulated, cell-specific and time-dependent processes. Among the proteins commonly regulated in the genetic models, guanylate binding protein 2 (GBP2) showed elevated levels in the vitreous that were accompanied by increased mRNA expression in the retina of both rod ΔVhl and all-cone ΔVhl mice. We hypothesize that some of the differentially regulated proteins at early time points may potentially be used as markers for the detection of a chronic hypoxic response of photoreceptors. Graphical abstract: Image 1 Highlights: Label-free shotgun proteomic analysis of mouse vitreous . 6 h acute hypoxia is sufficient to induce strong changes in the vitreous proteome . Chronic activation of a hypoxic response in rods and cones alters vitreous proteome .